Propranolol: a novel treatment for angiolymphoid hyperplasia with eosinophilia. (28th July 2014) - Horst, C.; Kapur, N.
Summary Angiolymphoid hyperplasia with eosinophilia (ALHE) is an uncommon, idiopathic disease that manifests as dermal or subcutaneous red or brown papules or nodules, most commonly on the head and neck. Histologically, ALHE is characterized by vascular proliferation with epithelioid endothelial cells with surrounding lymphocytic and eosinophilic infiltrate. There may be an accompanying serum eosinophilia and local lymphadenopathy. We report a case of a 32‐year‐old woman who presented with multiple erythematous nodules in the periauricular area and the vertex of her scalp. The nodules had been present for several months. Surgical removal of one of the lesions confirmed the histological diagnosis of ALHE. The patient was started on oral propranolol (40 mg once daily) in an effort to reduce the vascular component of the lesions. Within 6 weeks, the patient noted that several of the lesions had decreased in size, and all were less erythematous. Propranolol was subsequently stopped within a few months of initiating treatment. One lesion recurred over a year later, and propranolol was then restarted. No new lesions occurred after 2 years of follow‐up.